OPTIMALISASI PENERAPAN PERTANIAN ORGANIK BAGI PETANI DI NEGERI HARIA KECAMATAN SAPARUA KABUPATEN MALUKU TENGAH - H. Makaruku, Marlita; Wattimena, Anna Y.; L. Tanasale, Vilma; Goo, Nureny (HIRONO : Jurnal Pengabdian Masyarakat, 2023)
Organic farming is one of the environmentally sound cultivation technologies. This cultivation system will lead farmers to care more about the environment and pay more attention to environmental factors that exist in every farming activity that is carried out. Haria village is one of the village included in Saparua District which has potential in the agricultural sector. Community agricultural cultivation activities in Haria village are still carried out traditionally with the use of pesticides and chemical fertilizers to increase crop production, so that it can have a negative impact on nature and humans. The purpose of this community service activity is to increase the knowledge of the people of Negeri Haria in applying organic farming cultivation technology. This community service activity is carried out through the following stages: preparation, counseling, training, and activity evaluation. The results obtained from the implementation of this PKM activity are that the community gains knowledge about organic farming cultivation and how to make organic fertilizer